2015
DOI: 10.1016/j.wasman.2014.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of sludge composition on combustion performance derived from thermogravimetry analysis

Abstract: a b s t r a c tWastewater treatment plants produce millions of tons of sewage sludge. Sewage sludge is recognized as a promising feedstock for power generation via combustion and can be used for energy crisis adaption. We aimed to investigate the quantitative effects of various sludge characteristics on the overall sludge combustion process performance. Different types of sewage sludge were derived from numerous wastewater treatment plants in Beijing for further thermogravimetric analysis. Thermogravimetric-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(18 citation statements)
references
References 38 publications
0
15
0
3
Order By: Relevance
“…The most serious decline of 26.8% occurred when the scum sludge was dried from freeze-drying to oven-drying. Li et al (2015) reported that sludge combustion is significantly affected by protein, which is the main component of volatiles.…”
Section: Resultsmentioning
confidence: 99%
“…The most serious decline of 26.8% occurred when the scum sludge was dried from freeze-drying to oven-drying. Li et al (2015) reported that sludge combustion is significantly affected by protein, which is the main component of volatiles.…”
Section: Resultsmentioning
confidence: 99%
“…Sewage sludge is an undesired by-product of wastewater treatment, which needs to be treated, and otherwise, may have a significant environmental impact (Li et al 2015;Guo et al 2013;Semblante et al 2016). In Europe, the annual production of sewage sludge accounted for more than 10 million tons in 2010 and is expected to increase to 13 million tons in 2020 (Paul and Debellefontaine, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Las mezclas 1:9 y 3:7 registraron los mayores contenidos de MV y los valores más bajos de PCS, mientras que la mezcla 9:1 presentó los menores valores de MV. El contenido de MV del lodo se encuentra por debajo del reportado por (Li et al, 2015) quienes obtuvieron valores de MV entre 50 -74 %.…”
Section: Tabla 2 Resultados Obtenidos Del Análisis Próximo Totalunclassified
“…Equipos utilizados en el análisis próximo total y elemental azufre total y de PCS, mientras la mezcla 9:1 registró los menores contenidos de humedad residual (% HR) y cenizas (% Cz) y los más altos de azufre; en tanto el contenido de ceniza en las muestras de lodos fue de 57.92 %, superior al contenido de ceniza reportado por (Li et al, 2015) entre 23 y 47 %, quienes afirman que los valores obtenidos de humedad residual, MV, PCS., contenido de ceniza y azufre total durante la combustión de las mezclas puede ser debido al contenido de proteína presente en los lodos, la cual es el componente principal de la materia volátil. La mezcla 9:1 es más susceptible a generar altas emisiones de dióxido de azufre (SO 2 ) durante el proceso de combustión, puesto que esta mezcla contiene altos contenidos de azufre.…”
Section: Tabla 2 Resultados Obtenidos Del Análisis Próximo Totalunclassified
See 1 more Smart Citation